Mathematical Literacy of Prospective Teachers: A Systematic Review of Factors, Readiness, and Teacher Education Preparation - Dirgantoro, Kurnia Putri Sepdikasari; Kusumah, Yaya Sukjaya; Jupri, Al; Melissa, Margaretha Madha (FKIP Universitas Lampung, 2025)
Mathematical literacy is a crucial competency for 21st-century teachers to foster critical thinking and problem-solving skills in various educational contexts. However, several pieces of evidence suggest that many prospective teachers struggle to develop mathematical literacy, which may hinder the effectiveness of mathematics learning. This study aims to provide a comprehensive overview of the mathematical literacy of prospective teachers through a systematic literature review of previous research. The study used the PRISMA protocol by searching articles from five reputable databases (ERIC, ProQuest, Taylor & Francis, Emerald Insight, and Scopus) using predefined inclusion and exclusion criteria. Of the initial search results of 8659 articles, only 13 articles were eligible for further review after the screening and duplication removal process. The analysis was focused on six research questions which included: (1) the geographical distribution of the research, (2) the academic background of the research subject, (3) the research topic, (4) factors that affect mathematical literacy, (5) the readiness of prospective teachers, and (6) the form of debriefing by the teacher education program. The results showed that the mathematical literacy of prospective teachers was influenced by both internal factors, such as conceptual comprehension, self-efficacy, and anxiety, as well as external factors, including pedagogical training and sociocultural contexts. However, most teacher education programs have not optimally emphasized the development of contextual and applicative mathematical literacy. This study highlights the importance of strengthening the teacher education curriculum through a contextual, activity-based, and culturally responsive approach, enabling prospective teachers to develop and effectively implement mathematical literacy in diverse learning contexts. Keywords: mathematical literacy, prospective teacher, systematic review, teacher education, pedagogical preparation.